Contribution of Coronavirus-Specific Immunoglobulin G Responses to Complement Overactivation in Patients with Severe Coronavirus Disease 2019 . (10th March 2022) - Castanha, Priscila M S; Tuttle, Dylan J; Kitsios, Georgios D; Jacobs, Jana L; Braga-Neto, Ulisses; Duespohl, Matthew; Rathod, Sanjay; Marti, Michelle M; Wheeler, Sarah; Naqvi, Asma; Staines, Brittany; Mellors, John; et al.
Abstract: Background: Excessive complement activation has been implicated in the pathogenesis of coronavirus disease 2019 (COVID-19), but the mechanisms leading to this response remain unclear. Methods: We measured plasma levels of key complement markers, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA and antibodies against SARS-CoV-2 and seasonal human common cold coronaviruses (CCCs) in hospitalized patients with COVID-19 of moderate (n = 18) and critical severity (n = 37) and in healthy controls (n = 10). Results: We confirmed that complement activation is systemically increased in patients with COVID-19 and is associated with a worse disease outcome. We showed that plasma levels of C1q and circulating immune complexes were markedly increased in patients with severe COVID-19 and correlated with higher immunoglobulin (Ig) G titers, greater complement activation, and higher disease severity score. Additional analyses showed that the classical pathway was the main arm responsible for augmented complement activation in severe patients. In addition, we demonstrated that a rapid IgG response to SARS-CoV-2 and an anamnestic IgG response to the nucleoprotein of the CCCs were strongly correlated with circulating immune complex levels, complement activation, and disease severity. Conclusions: These findings indicate that early, nonneutralizing IgG responses may play a key role in complement overactivation in severe COVID-19. Our work underscores the urgent need to develop therapeutic strategies to modify complement overactivation in patients with COVID-19. Abstract : Our findings reveal that complement overactivation is mediated by the classical pathway in response to increased levels of circulating immune complexes and support the notion that an overexuberant immunoglobulin G response against severe acute respiratory syndrome coronavirus 2 and seasonal coronaviruses contributes to coronavirus disease 2019 severity.